2019
DOI: 10.2147/ndt.s197225
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical relevance of paliperidone palmitate 3-monthly in treating schizophrenia</p>

Abstract: Antipsychotics are the mainstay in schizophrenia management, and long-acting injectable (LAI) antipsychotics contribute to the successful maintenance of treatment by improving non-adherence and preventing relapses. Paliperidone palmitate 3-monthly (PP3M) formulation is the only available LAI antipsychotic that offers an extended 3-month window of stable plasma drug concentration, enabling only four injections per year. This paper summarizes clinically relevant endpoints from available evidence for PP3M to brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 111 publications
5
25
0
Order By: Relevance
“…A meta-analysis of studies of other atypical antipsychotics reported an overall mean response rate for long-acting injectables of 47% vs 24% for placebo (NNT = 4) based on a ≥20% improvement in PANSS total score;11 thus, AL 441 and 882 mg were comparable with respect to this outcome, with an observed NNT of 4 (95% CI: 3–6). Similar analyses have been published regarding other antipsychotics, including paliperidone palmitate,12,13 iloperidone,14 cariprazine,15 lurasidone,16 and pimavanserin 17…”
Section: Discussionsupporting
confidence: 70%
“…A meta-analysis of studies of other atypical antipsychotics reported an overall mean response rate for long-acting injectables of 47% vs 24% for placebo (NNT = 4) based on a ≥20% improvement in PANSS total score;11 thus, AL 441 and 882 mg were comparable with respect to this outcome, with an observed NNT of 4 (95% CI: 3–6). Similar analyses have been published regarding other antipsychotics, including paliperidone palmitate,12,13 iloperidone,14 cariprazine,15 lurasidone,16 and pimavanserin 17…”
Section: Discussionsupporting
confidence: 70%
“…This theory is supported with ndings from Weiden et al who compared time to relapse when oral paliperidone, PP1M and PP3M were discontinued; time to relapse was longest for PP3M, followed by PP1M, then oral paliperidone [30]. These ndings have also been corroborated by Mathews et al [29].…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have reported a reduced risk of rehospitalisation and relapse in patients receiving LAT compared with oral antipsychotic treatment [28][29][30]. A decrease in hospitalisation rate has also been demonstrated speci cally with the introduction of PP1M [31] and in those switching from PP1M to PP3M [14].…”
Section: Discussionmentioning
confidence: 94%
“…time to relapse was longest for PP3M, followed by PP1M, then oral paliperidone [30]. These ndings have also been corroborated by Mathews et al [29].…”
Section: Discussionmentioning
confidence: 53%